Study of magnetic and magnetocaloric effect of REMnO3(RE=Dy, Eu)manganites. Issue 10 (15th May 2022) - Wang, Qingwei; Yang, Hangfu; Luo, Xinyao; Fang, Jieyang; Yu, Nengjun; Wu, Qiong; Pan, Minxiang; Ge, Hongliang
Abstract: We have systematically investigated the magnetic and magnetocaloric effect (MCE) of REMnO3 (RE = Dy, Eu) manganites sintered by solid-state reaction method. The Neel temperature (TN ), the maximum magnetic entropy change (-ΔSm max ) and the relative cooling power (RCP) of the sample were obtained by measuring the magnetization and heat capacity. Under the magnetic field change of 50 kOe, large -ΔSm max of 8.93J/kg K and 9.31J/kg K are achieved around the TN of 14 K and 50 K for DyMnO3 and EuMnO3, respectively. It is proved by the slope of the Arrott plot and the universal phenomenological curve that the sample undergoes second order phase transition. The critical behavior of antiferromagnetic to paramagnetic phase transition is studied by modifying Arrott plot, which shows that the spin order of the sample decreases at the phase transition temperature and tends to change into shortrange order. The large magnetic entropy change calculated by Landau theory and experimental data indicates that the sample has a large magnetocaloric effect and has potential application in low temperature magnetic refrigeration materials.